How to talk to absolutely anyone : confident communication in every situation - Rhodes, Mark, 1966- (Capstone Pub., 2013)
BBe a people magnet!/b/ Improving your people skills and becoming a people-person is a surefire route to success, happiness, and confidence. Weive all looked enviously across the room at that person who seems to effortlessly interact with everyone ' humorous, confident and well liked. That person is confident with people they donit know, they have no fear of rejection, they can handle difficult situations with apparent ease. Well now you can too. iHow to Talk to Absolutely Anyone/i will show you exactly how to develop better communication for better results. With Mark Rhodes sound advice you will be able to build rapport with absolutely anyone. / /bLearn how to:/b / / Overcome fear of rejection / Be confident with people you donit know / Deal with difficult situations / Get better outcomes from disputes / Communicate better to win you more business and more sales / Be more effective at networking at both business and social /events.